A critical study of the Sistem Desa Bahagia (SDB) 2.0 as an innovation in fostering Pancasila values ​​for the younger generation - Devi Octavia Vijayanti; Encep Syarief Nurdin; Yadi Ruyadi (Inovasi Kurikulum, 2025)
Instilling Pancasila values in the younger generation is a strategic agenda in building a sustainable national character. The Sistem Desa Bahagia (SDB), as stipulated in Peraturan BPIP Nomor 3 Tahun 2022 Pasal 28, is designed to foster Pancasila values in Paskibraka candidates through training, education, and integrated parenting in a dormitory setting. The main objective is to shape attitudes, behaviors, and character based on Pancasila values through role modeling, collective habits, and strengthening discipline during the training period. However, during implementation, SDB faces various obstacles, including limitations in the operational curriculum and boarding facilities, and the absence of a standardized character evaluation system. This study employs a critical policy review approach to analyze gaps in the implementation of SDB. It proposes developing the SDB 2.0 concept as an innovation in Pancasila character development that is more systematic, reflective, and digitalized. By integrating the 5R curriculum (Reflection, Relation, Realization, Reconstruction, Recognition), habit formation based on boarding values, and the e-SDB platform, this concept is expected to serve as a strategic framework that strengthens the development of Pancasila values among the younger generation nationwide.   Abstrak Penanaman nilai-nilai Pancasila bagi generasi muda merupakan agenda strategis dalam membangun karakter kebangsaan yang berkelanjutan. Sistem Desa Bahagia (SDB) sebagaimana diatur dalam Peraturan BPIP Nomor 3 Tahun 2022 Pasal 28 dirancang sebagai metode pembinaan nilai-nilai Pancasila bagi calon Paskibraka melalui proses pelatihan, pendidikan, dan pengasuhan terpadu dalam suasana kehidupan asrama. Tujuan utamanya adalah membentuk sikap, perilaku, dan karakter berlandaskan nilai-nilai Pancasila melalui keteladanan, kebiasaan kolektif, serta penguatan disiplin selama masa pemusatan diklat. Namun, dalam implementasinya, SDB menghadapi berbagai kendala seperti keterbatasan kurikulum operasional, sarana boarding, serta belum adanya sistem evaluasi karakter yang terstandarisasi. Penelitian ini menggunakan pendekatan kajian kritis-kebijakan untuk menganalisis kesenjangan pelaksanaan SDB dan mengusulkan pengembangan konsep SDB 2.0 sebagai inovasi pembinaan karakter Pancasila yang lebih sistemik, reflektif, dan terdigitalisasi. Melalui integrasi kurikulum 5R (Refleksi, Relasi, Realisasi, Rekonstruksi, Rekognisi), pembiasaan nilai berbasis boarding, serta platform e-SDB, konsep ini diharapkan menjadi kerangka strategis yang memperkuat pembinaan nilai-nilai Pancasila bagi generasi muda secara nasional. Kata Kunci: 5R; karakter; Pancasila; pembinaan ideologi; SDB 2.0